ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA - Devi Ayu Putri (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2020)
This study aims to examine and analyze (1) the effect of profitability on the timeliness of financial reporting (2) the effect of leverage on the timeliness of financial reporting (3) the effect of company size on the timeliness of financial reporting (4) the effect of reputation of public accounting firms on the accuracy financial reporting time and (5) the influence of the audit committee on the timeliness of financial reporting of companies listed on the Indonesian stock exchange. This research was conducted in the manufacturing sector of the consumer goods sector in 2012-2016 on the Indonesia Stock Exchange. Methods of research data using non-participant observation methods, by analyzing the annual reports and audit financial reports obtained. The data analysis method is logistic regression analysis, with hypothesis testing carried out by multivariate testing. The results showed that the profitability and audit committee had a positive effect on the timeliness of financial reporting, while leverage, company size, reputation of public accounting firms had no effect on timeliness of financial reporting. This research is expected to provide significant implications for related parties in assessing and predicting the timeliness of financial report submission.